Thermal properties and Calcium-Magnesium-Alumina-Silicate (CMAS) resistance of LuPO4 as environmental barrier coatings. Issue 4 (April 2020) - Hu, Xunxun; Xu, Fangfang; Li, Kunwei; Zhang, Yizhou; Xu, Yue; Zhao, Xinqing
Abstract: LuPO4 ceramics have been synthesized by chemical precipitation and calcination approaches. The phase stability and the thermal properties of the ceramics as well as the thermochemical reactions between LuPO4 pellet and calcium–magnesium–alumina–silicate at 1300℃ have been investigated. The results indicated that LuPO4 has a relatively lower thermal conductivity (1.86 W m -1 K -1 at 1200 ℃) and a well-matched coefficient of thermal expansion (5.92 × 10 -6 K -1 ) with SiC based ceramic matrix composites. No phase transformation occurs in single phase LuPO4 during the heating from room temperature to 1300 ℃. Corrosion tests showed that CMAS can dissolve LuPO4 and cause precipitation of crystalline phases such as Lu2 Si2 O7, CaAl2 Si2 O8, CaMgSi2 O6, Ca2 Lu8 (SiO4 )6 O2 and Ca8 MgLu (PO4 )7 . Extending the corrosion duration results in the formation of Ca2 Lu8 (SiO4 )6 O2 apatite and other crystalline phases with a dendritic-like structure in the CMAS layer. CMAS corrosion resistance of LuPO4 is significantly greater than Lu2 Si2 O7 since less LuPO4 need to be dissolved to form a protective apatite barrier layer. Ca8 MgLu (PO4 )7 tends to form a continuous reaction layer at the CMAS/LuPO4 interface. This dense and continuous layer can effectively inhibit molten CMAS penetration into LuPO4 .